Draft Annual Plan 1986-87 Volume IV General Areas Government of Assam - Planning Commission (Planning Commission, 1986)
The physical achievement during the 6th Plan period is 2488 KMs of New Roads under MNP and OMNP and 694 KMs of blacktopped roads. The cumulative achievement is 21772 KMs of roads with 3998 KMs of surfaced roads.
Government of Assam, Planning and Development Department